2020
DOI: 10.5811/westjem.2020.7.48159
|View full text |Cite
|
Sign up to set email alerts
|

In-situ Simulation Use for Rapid Implementation and Process Improvement of COVID-19 Airway Management

Abstract: Introduction The coronavirus disease 2019 (COVID-19) pandemic presents unique challenges to frontline healthcare workers. In order to safely care for patients new processes, such as a plan for the airway management of a patient with COVID-19, must be implemented and disseminated in a rapid fashion. The use of in-situ simulation has been used to assist in latent problem identification as part of a Plan-Do-Study-Act cycle. Additionally, simulation is an effective means for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…We developed a structured curriculum to teach appropriate donning and doffing of PPE and a modified airway management algorithm for suspected COVID-19 patients using in situ simulation. 8 , 9 The modified airway management algorithm and simulation scenario were developed by institutional leaders, including our initial trainer (C.H.H. ), who had experience in health care operations, education, and critical care.…”
Section: Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…We developed a structured curriculum to teach appropriate donning and doffing of PPE and a modified airway management algorithm for suspected COVID-19 patients using in situ simulation. 8 , 9 The modified airway management algorithm and simulation scenario were developed by institutional leaders, including our initial trainer (C.H.H. ), who had experience in health care operations, education, and critical care.…”
Section: Approachmentioning
confidence: 99%
“…), who had experience in health care operations, education, and critical care. 8 , 9 The algorithm was tested and revised multiples times using the plan–do–study–act process and feedback from its use in both the simulated and clinical environments. 8 , 9 Our prior work had demonstrated that learners achieved significant improvement in comfort with donning and doffing PPE, role identification, and AGP management for suspected COVID-19 patients after the in situ simulation.…”
Section: Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires extensive staff training, buddy systems, practice through simulation, and ongoing feedback to combat 'pandemic fatigue' . 39,40 With rigorous IPC practices, it may be possible to greatly limit or even prevent any staff infections in the workplace. 3…”
Section: Prevent Protect and Preparementioning
confidence: 99%
“…recommendations by the scientific sections' collaborative of the european society of pediatric and neonatal intensive care. Pediatr Crit Care Med 2021;22(01):56-67 2 Álvarez Z P, Larios G G, Toro R L, et al Recommendation for the recognition, management and follow up of cardiovascular compromise in patients with pediatric multisystemic inflammatory syndrome associated with COVID-19 (PIMS-CT). Position statement of Chilean Scientific Societies [in Spanish].…”
mentioning
confidence: 99%